Extracolonic Cancer in Inflammatory Bowel Disease: Data from the GETECCU Eneida Registry. (July 2017) - Chaparro, María; Ramas, M; Benítez, J M; López‐García, A; Juan, A; Guardiola, J; Mínguez, M; Calvet, X; Márquez, L; Salazar, L I Fernández; Bujanda, L; García, C; et al.
Abstract : Objectives: The objective of this study was (a) To know the prevalence and distribution of extracolonic cancer (EC) in patients with inflammatory bowel disease (IBD); (b) To estimate the incidence rate of EC; (c) To evaluate the association between EC and treatment with immunosuppressants and anti‐tumor necrosis factor (TNF) agents. Methods: This was an observational cohort study. Inclusion criteria: IBD and inclusion in the ENEIDA Project (a prospectively maintained registry) from GETECCU. Exclusion criteria: Patients with EC before the diagnosis of IBD, lack of relevant data for this study, and previous treatment with immunosuppressants other than corticosteroids, thiopurines, methotrexate, or anti‐TNF agents. The Kaplan–Meier method was used to evaluate the impact of several variables on the risk of EC, and any differences between survival curves were evaluated using the log‐rank test. Stepwise multivariate Cox regression analysis was used to investigate factors potentially associated with the development of EC, including drugs for the treatment of IBD, during follow‐up. Results: A total of 11, 011 patients met the inclusion criteria and were followed for a median of 98 months. Forty‐eight percent of patients (5, 303) had been exposed to immunosuppressants or anti‐TNF drugs, 45.8% had been exposed to thiopurines, 4.7% to methotrexate, and 21.6% to anti‐TNF drugs. The prevalence of EC was 3.6%. In the multivariate analysis, age (HR=1.05, 95% CI=1.04–1.06) and having smoked (hazards ratio (HR)=1.47, 95% confidence interval (CI)=1.10–1.80) were the only variables associated with a higher risk of EC. Conclusions: Neither immunosuppressants nor anti‐TNF drugs seem to increase the risk of EC. Older age and smoking were associated with a higher prevalence of EC.